The moderating effect of brand trust on the relationship between customer brand engagement and brand loyalty: a conceptual review / Nurul Aqmar Zaidun, Mazzini Muda and Nor Hashima Hashim - Zaidun, Nurul Aqmar; Muda, Mazzini; Hashim, Nor Hashima (Universiti Teknologi Mara Selangor, 2020)
Brand loyalty has become a primary goal for a company in today’s business environment due to intense market competition. Therefore, companies need to engage with customers, as this may result in brand loyalty. Drawing from Dick and Basu customer loyalty model, this paper propose a conceptual framework on customer brand engagement, customer loyalty and brand trust. In addition, brand trust has received extensive attention and widely recognised as an essential variable that affects human relationships at all levels. Although the relationship between brand trust and brand loyalty has been widely discussed, however, how brand trust develops remains uncertain. Therefore, trust as a moderating variable trust is introduced in the conceptual framework to determine if there exist positive behavioural outcomes.